International Monetary Fund Annual Report 2019 : Our Connected World. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2019)
This issue of Annual Report discusses that the global economy is at a delicate moment. The expansion of early 2018 has lost momentum, in large part in response to rising trade tensions. There are threats from rising financial vulnerabilities and geopolitical uncertainties. These challenges call for policymakers to avoid missteps and to take the right policy steps: at home, across borders, and globally. In addition to several major reviews looking at IMF conditionality, economic and financial surveillance, and lending facilities, the management has deepened its analysis on trade spillovers and financial stability and are revamping frameworks for debt sustainability assessment in low-income and market access countries. Building on earlier research that showed how trade can boost incomes and living standards by enabling the flow of technology across countries, the October 2018 World Economic Outlook provided illustrative scenarios of the potential impact of escalating trade tensions between the United States and China.